2021
DOI: 10.14260/jemds/2021/717
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Assisted Vaginal Deliveries in a Tertiary Care Centre in Bengaluru

Abstract: BACKGROUND The lower segment caesarean section (LSCS) audit shows an increase in caesarean section rates worldwide. Assisted vaginal delivery and, if needed, emergency caesarean section are options available to the obstetrician to handle challenges in the second stage when spontaneous and safe delivery is not imminent. Judicious use of the instrument as well as continuing medical education in the art of assisted vaginal delivery is a must to achieve the twin goal of containing the surging caesarean section rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…3 Another study conducted at a tertiary care centre in Bangalore showed the rate of forceps assisted deliveries to be 3.9%. 4 But rate of these injuries are decreasing in today's era due to advances in the technique of delivery and increasing rates of caesarean sections. 5 Nevertheless, there are certain situations where the obstetrician still has to use forceps to deliver the foetus during labour.…”
Section: Introductionmentioning
confidence: 99%
“…3 Another study conducted at a tertiary care centre in Bangalore showed the rate of forceps assisted deliveries to be 3.9%. 4 But rate of these injuries are decreasing in today's era due to advances in the technique of delivery and increasing rates of caesarean sections. 5 Nevertheless, there are certain situations where the obstetrician still has to use forceps to deliver the foetus during labour.…”
Section: Introductionmentioning
confidence: 99%